2011
DOI: 10.1177/1938640010397341
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hamstring Tightness in Plantar Fasciitis

Abstract: The purpose of this prospective cohort study was to determine if hamstring tightness was an increased risk in plantar fasciitis. It was thought that there is an increased risk of plantar fasciitis when hamstring tightness is present. A total of 105 patients (68 women, 37 men) were included in the study, 79 of whom were diagnosed with plantar fasciitis. Body mass index (BMI) was calculated and the presence of plantar fasciitis, equinus, and calcaneal spurs were assessed. The popliteal angle was measured using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 16 publications
2
39
0
Order By: Relevance
“…The results of current study support study of Labovitz [5] who observed that patients had hamstring tightness were about 8.7 times as likely to be plantar fasciitis patients [5] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of current study support study of Labovitz [5] who observed that patients had hamstring tightness were about 8.7 times as likely to be plantar fasciitis patients [5] .…”
Section: Discussionsupporting
confidence: 89%
“…Incidence of plantar fasciitis in patients with hamstring tightness is 8.7 times if compared with patients without hamstring tightness [5] .…”
Section: Introductionmentioning
confidence: 91%
“…Reduced range of ankle dorsiflexion is associated with plantar fasciitis, 6 as are calf and hamstring tightness. 15 What is the differential diagnosis?…”
Section: Who Gets Plantar Fasciitis?mentioning
confidence: 99%
“…The fact that rupture of the plantar fascia has been reported to sometimes cure the condition 11 suggests that surgical division of the origin (performed with open or arthroscopic technique) might give success in resistant cases. Although hamstring and calf tightness are associated with plantar fasciitis, 15 cause and effect has not been proved, and it may be that these phenomena are all caused by subtle L5 and S1 nerve impingement in older people. 48 Good results obtained from gastrocnemius release in plantar fasciitis 47 49 either supports a role for aetiology or suggests that much of the success of surgery may be due to a prolonged period of unloading and reloading.…”
Section: Surgerymentioning
confidence: 99%
“…[345] Reduced range of ankle dorsiflexion is associated with plantar fasciitis,[3] as are calf and hamstring tightness. [6]…”
Section: Introductionmentioning
confidence: 99%